Potential Biotechnological Applications of Venoms from the Viperidae Family in Central America for Thrombosis - Chang Estrada, Jorge Eduardo; Guerrero, Taissa Nunes; Reyes-Enríquez, Daniel Fernando; Nardy, Erica Santos; Guimarães Ferreira, Roseane; Ruiz Calderón, Cristian José; Wellmann, Irmgardt A.; Monteiro Espíndola, Kaio Murilo; do Prado, Alejandro Ferraz; Soares, Andreimar Martins; Fontes, Marcos Roberto de Mattos [UNESP]; Chagas Monteiro, Marta; et al. (MDPI, 2024)
Central America is home to one of the most abundant herpetofauna in the Americas, occupying only 7% of the continent’s total area. Vipers and lizards are among the most relevant venomous animals in medical practice due to the consequences of envenomation from the bite of these animals. A great diversity of biomolecules with immense therapeutic and biotechnological value is contained in their venom. This paper describes the prominent leading representatives of the family Viperidae, emphasizing their morphology, distribution, habitat, feeding, and venom composition, as well as the biotechnological application of some isolated components from the venom of the animals from these families, focusing on molecules with potential anti-thrombotic action. We present the leading protein families that interfere with blood clotting, platelet activity, or the endothelium pro-thrombotic profile. In conclusion, Central America is an endemic region of venomous animals that can provide many molecules for biotechnological applications.
Keywords: biomolecules; envenomation; thrombosis; venom; Viperidae